Analysis of The Competitiveness of Coffee Agroindustry in Sleman Regency - Erista Adisetya; Andreas Wahyu Krisdiarto; Ida Bagus Banyuro Partha; Priyambodo Priyambodo (Tropical Plantation Journal, 2022)
Coffee is one of the commodities that are growing and popular today, especially with the rise of coffee shops and cafes along with the improvement of the tourism sector after the covid-19 pandemic subsided. This research aims to find out the competitiveness of merapi coffee agroindustry in Sleman regency. Competitiveness analysis is done quantitatively with the Policy Analysis Matrix (PAM) method approach to find out comparative advantage and competitive advantage, while qualitative analysis uses the Porter Diamond model method. Data collection is done by snow ball sampling through interviews and from secondary sources. Qualitative competitiveness analysis of Sleman coffee agroindustry is carried out on conditions, demand conditions, supporting industries and strategies, competitive structures and conditions. The results showed that coffee agroindustrials in Sleman have a comparative advantage in the absence of policies or added value generated beyond the cost (DRCR value) (Domestic Resources Cost Ratio) = 0.83. Coffee Agroindustry in Sleman also has a competitive advantage, indicated by a PCR (Private Cost Ratio) value = 0.41. The competitiveness of the merapi coffee agroindustrial industry is supported by soil fertility in the Mount Merapi area, increased demand for coffee due to the development of coffee shops and cafés, support from the Sleman tourism industry and local governments. Sleman coffee agroindustrials need to be developed from the marketing side to increase brand equity.